Useless Joyce : textual functions, cultural appropriations - Conley, Tim, 1972- (Toronto : University of Toronto Press, 2017)
Tim Conley's Useless Joyce provocatively analyses Joyce's Ulysses and Finnegans Wake and takes the reader on a journey exploring the perennial question of the usefulness of literature and art. Conley argues that the works of James Joyce, often thought difficult and far from practical, are in fact polymorphous meditations on this question. Examinations of traditional textual functions such as quoting, editing, translating, and annotating texts are set against the ways in which texts may be assigned unexpected but thoroughly practical purposes. Conley's accessible and witty engagement with the material views the rise of explication and commentary on Joyce's work as an industry not unlike the rise of self-help publishing. We can therefore read Ulysses and Finnegans Wake as various kinds of guides and uncover new or forgotten "uses" for them. Useless Joyce invites new discussions about the assumptions at work behind our definitions of literature, interpretation, and use
Introduction -- Part one: textual functions -- Guidance systems -- Misquoting Joyce -- Limited editions, edited limitations -- Translation, annotation, hesitation -- Part two: cultural appropriations -- Make a stump speech out of it -- Win a dream date with James Joyce -- The Stephen Dedalus diet -- Conclusion: means without end.
Includes bibliographical references and index.
Print version of record.
JSTOR
Keywords: Joyce, James, -- 1882-1941 -- Criticism and interpretation; Joyce, James, -- 1882-1941.; Joyce, James, -- 1882-1941.; Joyce, James, -- 1882-1941; Finnegans wake (Joyce, James); Ulysses (Joyce, James); Art and literature; Art et littérature.; LITERARY CRITICISM -- European -- English, Irish, Scottish, Welsh; Art and literature; Criticism, interpretation, etc